Prediction of the Behavior Towards Personal Protective Equipment Use in the Ghanaian Construction Sector: Application of the Extended Theory of Planned Behavior - Maxwell Kwame Boakye; Elom Ayeke; Patricia Asantewaa-Tannor; Augustine Korli Lawer; Ruby Nsakie; Christopher Adu-Gyamfi; Abdul-Aziz (Occupational Health and Safety Society of Nepal, 2024)
Introduction: The construction industry experiences a high rate of fatalities and injuries due to unsafe behavior at the workplace. Personal Protective Equipment (PPE) effectively prevents occupational accidents, but compliance with its use is not always guaranteed due to unsafe behavior. However, the drivers of PPE use behavior among Ghanaian construction workers are poorly understood. This study aimed to identify the determinants of PPE use behavior among building construction students using the Theory of Planned Behavior (TPB) and the additional construct of perceived threat. Methods: Data was collected from 250 building construction students from Ho Technical University using a structured questionnaire. A stepwise multiple logistic regression was used to assess factors influencing PPE use behavior. Results: The study revealed that the six constructs explained 94% of variance in self-reported PPE use behavior. The intention construct was found to be the strongest predictor of PPE use behavior. Aside from intention, perceived severity was a better predictor of PPE use behavior among all the other constructs. Conclusion: This finding suggests that the higher the perceived severity, the more likely the students will use PPE to mitigate the risks of exposure to hazards. The findings underlined the importance of emphasizing the severity of occupational injuries from construction activities to improve PPE use behavior.